High-strength low-alkali Portland cement and preparation method thereof

By introducing hazardous waste materials and controlling calcination parameters during the preparation process of silicate cement, the shortcomings of existing cement in hazardous waste treatment and chemical erosion environments are solved, and the preparation of high-strength, low-alkali silicate cement is realized, and resource utilization and performance are improved.

CN119528463APending Publication Date: 2025-02-28CHINA UNITED CEMENT NANJING
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411609582.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Existing silicate cement has problems of insufficient resource utilization and high energy consumption when dealing with hazardous waste, and it performs poorly in an environment eroded by chemical substances.

Method used

By selecting lime slag, silicon-aluminum raw materials and iron raw materials as raw materials, and introducing hazardous waste materials during the calcination process, controlling the calcination temperature and kiln speed, and adjusting the sulfur-base ratio in the clinker to prepare high-strength low-alkali silicate cement.

Benefits of technology

It realizes the resource treatment of hazardous waste materials, reduces energy consumption, improves the strength and stability of cement, and is suitable for special concrete projects that require high strength and low alkalinity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528463A_ABST
    Figure CN119528463A_ABST
Patent Text Reader

Abstract

The invention provides high-strength low-alkali Portland cement and a preparation method thereof, and relates to the technical field of cement. The preparation method provided by the invention comprises the following steps: S1, selecting raw materials; s2, mixing, grinding and homogenizing the raw materials to form raw material powder; s3, calcining the raw material powder to prepare clinker, and adding dangerous waste materials in the calcining process; s4, the clinker prepared through calcination is cooled, crushed and ground into powder, and the cement is obtained.The calcination temperature, the kiln speed and combustion atmosphere parameters are controlled, and the sulfur-alkali ratio in the final clinker is controlled, so that the burnability of the raw material is improved, the calcination temperature is lowered, energy consumption is reduced, the production efficiency of the clinker is improved, and the strength and stability of the clinker are effectively improved; and meanwhile, the hazardous waste materials are co-treated, so that the recycling treatment and utilization of the hazardous waste materials are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of cement, and in particular to a high-strength, low-alkali silicate cement and a preparation method thereof. Background Art

[0002] Ordinary Portland cement is mainly made of materials such as limestone and clay. Its main physical properties are high early strength, fast setting and hardening, and good frost resistance, but it has high hydration heat and poor alkali and sulfate corrosion resistance. Therefore, it is not suitable for projects subject to chemical corrosion. High-strength low-alkali Portland cement has higher strength. At the same time, due to its low alkali content, it has a positive effect on the hardening process and long-term performance of concrete. It can be used in special concrete projects that require high strength and low alkalinity.

[0003] During the sludge treatment and production process of chemical enterprises, many hazardous waste materials are generated, such as sludge, organic solvents, filter residues, residues, distillation residues, activated carbon, waste oil, waste liquid, etc. These hazardous waste materials contain the elements needed for silicate cement. If they are used to make high-strength low-alkali silicate cement, they can effectively treat hazardous waste materials, save energy and protect the environment, and achieve resource recycling.

[0004] In view of this, the present application aims to provide a high-strength, low-alkali silicate cement and a preparation method thereof, so as to better solve the above-mentioned technical problems. Summary of the invention

[0005] The purpose of the embodiments of the present application is to provide a high-strength low-alkali silicate cement and a preparation method thereof, which utilizes hazardous waste materials to produce high-strength low-alkali silicate cement, thereby solving the technical problem of resource disposal of hazardous waste materials.

[0006] The present invention provides a method for preparing high-strength low-alkali silicate cement, comprising the following steps:

[0007] S1. Select 85%-90% limestone slag, 4%-13% silicon-aluminum raw materials and 2%-6% iron raw materials as raw materials;

[0008] S2. The raw materials are mixed, ground, and homogenized to form raw powder;

[0009] S3. The raw material powder is calcined into clinker, and hazardous waste materials not exceeding 1% of the raw material feed amount are added during the calcination process. The kiln temperature during the calcination process is controlled to be 1450-1600°C, the kiln speed is 3.5-4.0rpm, and preheated air is used as the calcination atmosphere;

[0010] S4. After the calcined clinker is cooled, it is crushed and ground to obtain cement.

[0011] Furthermore, in step S1, the chemical composition of the raw material is 41.5-42.5% calcium oxide, 12-14% silicon dioxide, 2.5-3.5% aluminum oxide, 2.3-2.6% iron oxide, 0.1-0.15% sodium oxide, 0.2-0.3% potassium oxide, and 1.0-2.0% magnesium oxide.

[0012] Furthermore, in step S3, a preheater is used to preheat the air, and the oxygen content of the air at the outlet of the preheater is controlled to be 2%-3.5%.

[0013] Furthermore, in step S3, the combination is pre-calculated based on the chemical composition of the raw material and the chemical composition of the hazardous waste material to adjust the sulfur-alkali ratio during the clinker calcination process, and the sulfur-alkali ratio in the final clinker is controlled to be 0.8-1.0%.

[0014] Furthermore, in step S3, the coal ash sedimentation rate during the calcination process is controlled to be 2.1-2.8%.

[0015] Furthermore, in step S3, the hazardous waste material is composed of any of sludge, organic solvent, filter residue, distillation residue, activated carbon, waste oil, waste and waste liquid.

[0016] Furthermore, in step S3, the mass proportions of the components in the hazardous waste material are 50-60% sludge, 0-1% organic solvent, 10-15% filter residue, 3-12% distillation residue, 0-2% activated carbon, 3-6% waste oil, 0-1% waste, and 5-10% waste liquid.

[0017] Furthermore, in step S3, the chemical composition of each component in the hazardous waste material is:

[0018] Sludge: Al2O3 0-7%, CaO 0-5%, Fe2O3 0-6%, K2O 0-1%, SiO2 0-8%, Cl 0-1%, S 0-1%, Cr 0-0.045%;

[0019] Organic solvent: Al2O3 0-7%, CaO 0-3%, Fe2O3 0-4%, K2O 0-1.3%, SiO2 0-7%, Cl 0-1%, S 0-1%, Cr 0-0.045%;

[0020] Filter residue: Al2O30-12%, CaO 0-13%, Fe2O30-50%, K2O 0-1%, SiO20-7%, Cl 0-5%, S0-5%, Cr 0-0.4%;

[0021] Distillation residue: Al2O3 0-7%, CaO 0-2%, Fe2O3 0-0.1%, K2O 0-3%, SiO2 0-5%, Cl 0-1%, S 0-1%, Cr 0-0.045%;

[0022] Activated carbon: Al2O3 0-11%, CaO 0-12%, Fe2O3 0-6%, K2O 0-5%, SiO2 0-8%, Cl 0-1%, S0-1%, Cr 0-0.045%;

[0023] Waste oil: Al2O3 0-4%, CaO 0-4%, Fe2O3 0-5%, K2O 0-3%, SiO2 0-10%, Cl 0-1%, S 0-1%, Cr 0-0.045%;

[0024] Waste: Al2O3 0-4%, CaO 0-0.2%, Fe2O3 0-0.15%, K2O 0-1%, SiO2 0-3%, Cl 0-1%, S 0-1%, Cr 0-0.045%;

[0025] Waste liquid: Al2O3 0-7%, CaO 0-4%, Fe2O3 0-4%, K2O 0-5%, SiO2 0-7%, Cl 0-1%, S 0-1%, Cr 0-0.045%.

[0026] Based on the same inventive concept, the present application also provides a high-strength, low-alkali silicate cement prepared using the above-mentioned preparation method, and the strength grade of the cement is not less than grade 42.5.

[0027] Beneficial effects of the present invention:

[0028] The preparation method of high-strength low-alkali Portland cement provided by the present invention controls the sulfur-alkali ratio in the final clinker by controlling the calcination temperature, kiln speed and combustion atmosphere parameters, so as to improve the burnability of the raw material, reduce the calcination temperature, reduce energy consumption, improve the production efficiency of the clinker, and effectively improve the strength and stability of the clinker, while coordinating the disposal of hazardous waste materials to achieve resource-based treatment and utilization of hazardous waste materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0030] Figure 1 This is the process flow of the present invention. DETAILED DESCRIPTION

[0031] The present invention will be further described in detail below in conjunction with specific examples, but the embodiments of the present invention are not limited to the scope represented by the examples. These examples are only used to illustrate the present invention, but are not used to limit the scope of the present invention. In addition, after reading the content of the present invention, those skilled in the art can make various modifications to the present invention, and these equivalent changes also fall within the scope limited by the appended claims of the present invention.

[0032] It should be noted here that in the following embodiments of the present application, the specific method of "pre-calculating and matching based on the chemical composition of the raw material and the chemical composition of the hazardous waste material to adjust the sulfur-alkali ratio during the clinker calcination process" is as follows:

[0033] For example, the raw material ratio is: limestone accounts for 90%, clay accounts for 6%, and copper tailings accounts for 4%, of which the sodium oxide and potassium oxide in limestone are 0.12% and 0.25% respectively, the sodium oxide and potassium oxide in clay are 0.65% and 1.16% respectively, and the sodium oxide and potassium oxide in copper tailings are 0.14% and 0.2% respectively.

[0034] The contents of sodium oxide and potassium oxide in the raw meal are:

[0035] Sodium oxide mass percentage content = 90% * 0.12% + 6% * 0.65% + 4% * 0.14% = 0.1306%

[0036] Potassium oxide mass percentage content = 90% * 0.25% + 6% * 1.16% + 4% * 0.2% = 0.3026%

[0037] Raw material alkali content mass percentage content = 0.1306% + 0.658 * 0.3026% = 0.2937%

[0038] The actual clinker alkali content includes the hazardous waste alkali content, raw material alkali content, and coal ash sedimentation alkali content.

[0039] For example, in actual production, the raw material input is 380t / h, the hazardous waste input is basically 1% of the raw material feed, and the coal ash sedimentation rate is 2.81%. The sodium oxide and potassium oxide in the hazardous waste are 3.31% and 0.38% respectively, and the sodium oxide and potassium oxide in the coal ash are 0.08% and 0.15% respectively.

[0040] Then the alkali content of each ton of hazardous waste = 3.31% + 0.658*0.38% = 3.58%

[0041] The actual alkali content of the clinker = 3.58% * 1% = 0.0358%

[0042] Alkali content per ton of coal ash = 0.08% + 0.15% * 0.658 = 0.1787%

[0043] The actual alkali content of the clinker = 0.1787% * 2.81% = 0.005%

[0044] Theoretical clinker alkali content = 0.2937% * 1.52 + 0.0358% + 0.005% = 0.4872%

[0045] Based on this calculation method, the sulfur-alkali ratio is adjusted during the clinker calcination process, and the sulfur-alkali ratio in the final clinker is controlled to be 0.8-1.0%.

[0046] The following are specific embodiments

[0047] Example 1

[0048] The embodiment provides a method for preparing high-strength low-alkali silicate cement, comprising the following steps:

[0049] S1. Select raw materials, in which limestone accounts for 90%, clay accounts for 6%, and copper tailings accounts for 4%, wherein the sodium oxide and potassium oxide in limestone are 0.12% and 0.25% respectively, the sodium oxide and potassium oxide in clay are 0.65% and 1.16% respectively, and the sodium oxide and potassium oxide in copper tailings are 0.14% and 0.2% respectively;

[0050] S2. The raw materials are mixed, ground, and homogenized to form raw powder;

[0051] S3. The raw material powder is calcined into clinker, and 1% of hazardous waste materials (60% sludge, 1% organic solvent, 12% filter residue, 11% distillation residue, 2% activated carbon, 3% waste oil, 1% laboratory waste, 10% waste liquid) are added to the raw material feed during the calcination process. The coal ash settling rate is 2.81%. At the same time, the kiln temperature during the calcination process is controlled to be 1480°C, the kiln speed is 3.7rpm, and the air preheated by the preheater is used as the calcination atmosphere, and the oxygen content at the preheater outlet is 2.1%;

[0052] Among them, the theoretical clinker alkali content is 0.4872%;

[0053] S4. After the calcined clinker is cooled, it is crushed and ground to obtain cement.

[0054] Example 2

[0055] The embodiment provides a method for preparing high-strength low-alkali silicate cement, comprising the following steps:

[0056] S1. Select raw materials, in which limestone accounts for 89%, clay accounts for 6.5%, and copper tailings account for 4.5%, wherein the sodium oxide and potassium oxide in limestone are 0.08% and 0.21% respectively, the sodium oxide and potassium oxide in clay are 0.58% and 1.02% respectively, and the sodium oxide and potassium oxide in copper tailings are 0.11% and 0.22% respectively;

[0057] S2. The raw materials are mixed, ground, and homogenized to form raw powder;

[0058] S3. The raw material powder is calcined into clinker, and 1% of hazardous waste materials (60% sludge, 1% organic solvent, 15% filter residue, 8% distillation residue, 2% activated carbon, 3% waste oil, 1% laboratory waste, 10% waste liquid) are added to the raw material feed during the calcination process. The coal ash settling rate is 2.43%. At the same time, the kiln temperature during the calcination process is controlled to be 1560°C, the kiln speed is 3.8rpm, and the air preheated by the preheater is used as the calcination atmosphere, and the oxygen content at the preheater outlet is 2.3%;

[0059] Among them, the theoretical clinker alkali content is 0.4737%;

[0060] S4. After the calcined clinker is cooled, it is crushed and ground to obtain cement.

[0061] Example 3

[0062] The embodiment provides a method for preparing high-strength low-alkali silicate cement, comprising the following steps:

[0063] S1. Select raw materials, in which limestone accounts for 88.5%, clay accounts for 7.5%, and copper tailings account for 4%, wherein the sodium oxide and potassium oxide in limestone are 0.10% and 0.23% respectively, the sodium oxide and potassium oxide in clay are 0.61% and 0.96% respectively, and the sodium oxide and potassium oxide in copper tailings are 0.15% and 0.18% respectively;

[0064] S2. The raw materials are mixed, ground, and homogenized to form raw powder;

[0065] S3. The raw material powder is calcined into clinker, and 1% of hazardous waste materials (60% sludge, 1% organic solvent, 10% filter residue, 15% distillation residue, 1% activated carbon, 3% waste oil, 1% laboratory waste, 9% waste liquid) are added to the raw material feed during the calcination process. The coal ash settling rate is 2.6%. At the same time, the kiln temperature during the calcination process is controlled to be 1465°C, the kiln speed is 3.6rpm, and the air preheated by the preheater is used as the calcination atmosphere, and the oxygen content at the preheater outlet is 2.35%;

[0066] Among them, the theoretical clinker alkali content is 0.5338%;

[0067] S4. After the calcined clinker is cooled, it is crushed and ground to obtain cement.

[0068] Example 4

[0069] The embodiment provides a method for preparing high-strength low-alkali silicate cement, comprising the following steps:

[0070] S1. Select raw materials, in which limestone accounts for 88%, clay accounts for 8%, and copper tailings account for 4%, wherein the sodium oxide and potassium oxide in limestone are 0.07% and 0.18% respectively, the sodium oxide and potassium oxide in clay are 0.63% and 0.95% respectively, and the sodium oxide and potassium oxide in copper tailings are 0.16% and 0.21% respectively;

[0071] S2. The raw materials are mixed, ground, and homogenized to form raw powder;

[0072] S3. The raw material powder is calcined into clinker, and 1% of hazardous waste materials (60% sludge, 10% filter residue, 15% distillation residue, 1% activated carbon, 4% waste oil, 10% waste liquid) are added to the raw material feed during the calcination process. The coal ash settling rate is 2.32%. At the same time, the kiln temperature during the calcination process is controlled to be 1530°C, the kiln speed is 3.8rpm, and the air preheated by the preheater is used as the calcination atmosphere, and the oxygen content at the preheater outlet is 2.26%;

[0073] Among them, the theoretical clinker alkali content is 0.4605%;

[0074] S4. After the calcined clinker is cooled, it is crushed and ground to obtain cement.

[0075] Example 5

[0076] The embodiment provides a method for preparing high-strength low-alkali silicate cement, comprising the following steps:

[0077] S1. Select raw materials, in which limestone accounts for 86%, clay accounts for 9.5%, and copper tailings account for 4.5%. The sodium oxide and potassium oxide in limestone are 0.08% and 0.18% respectively, the sodium oxide and potassium oxide in clay are 0.71% and 1.05% respectively, and the sodium oxide and potassium oxide in copper tailings are 0.13% and 0.17% respectively;

[0078] S2. The raw materials are mixed, ground, and homogenized to form raw powder;

[0079] S3. The raw material powder is calcined into clinker, and 1% of hazardous waste materials (60% sludge, 1% organic solvent, 12% filter residue, 15% distillation residue, 2% activated carbon, 10% waste liquid) are added to the raw material feed during the calcination process. The coal ash settling rate is 2.35%. At the same time, the kiln temperature during the calcination process is controlled to be 1580°C, the kiln speed is 3.9rpm, and the air preheated by the preheater is used as the calcination atmosphere, and the oxygen content at the preheater outlet is 2.51%;

[0080] Among them, the theoretical clinker alkali content is 0.5116%;

[0081] S4. After the calcined clinker is cooled, it is crushed and ground to obtain cement.

[0082] The composition and performance of the cements prepared in the above Examples 1-5 were tested in accordance with the cement chemical analysis method: GB / T176.

[0083] The results of the ingredient tests are shown in the following table:

[0084]

[0085]

[0086] The performance test results are shown in the following table:

[0087]

[0088] Based on the above performance test table, it can be seen that the specific surface area of ​​the cement prepared in the embodiment of the present application is between 354 and 365, with a small fluctuation range and good preparation stability. At the same time, it has a higher specific surface area, indicating that the particle size distribution is more uniform, the cement particles are finer, and the hydration reaction is faster, which is conducive to the early development of strength; its fineness value is between 8.1 and 9.5, with a moderate range, which can further ensure the hydration reaction during use, as well as higher strength; the consistency value of the cement prepared in the embodiment of the present application is relatively stable, between 27.2 and 27.6, and the initial setting time is between 145 and 224 minutes, and the final setting time is between 191 and 289 minutes, with good construction performance; the 3-day flexural strength of the cement prepared in this embodiment is between 5.8 and 6.6 MPa, and the 3-day compressive strength is between 28.4 and 31.8 MPa, which has higher strength, thereby better meeting the application scenarios of high-strength cement.

[0089] In summary, the preparation method provided in the present application controls the sulfur-alkali ratio in the final clinker by controlling the calcination temperature, kiln speed and combustion atmosphere parameters, so as to improve the burnability of the raw material, reduce the calcination temperature, reduce energy consumption, improve the production efficiency of the clinker, and effectively improve the strength and stability of the clinker. The prepared cement is relatively stable in terms of specific surface area, fineness and consistency, and has high strength, which can better meet application needs. At the same time, it can coordinate the disposal of hazardous waste materials and realize the resource utilization of hazardous waste materials, and has good application prospects.

[0090] The above are only preferred embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A method for preparing high-strength low-alkali silicate cement, characterized in that: The steps include: S1. Select 85%-90% limestone slag, 4%-13% silicon-aluminum raw materials and 2%-6% iron raw materials as raw materials; S2. The raw materials are mixed, ground, and homogenized to form raw powder; S3. The raw material powder is calcined into clinker, and hazardous waste materials not exceeding 1% of the raw material feed amount are added during the calcination process. The kiln temperature during the calcination process is controlled to be 1450-1600°C, the kiln speed is 3.5-4.0rpm, and preheated air is used as the calcination atmosphere; S4. After the calcined clinker is cooled, it is crushed and ground to obtain cement.

2. The method for preparing high-strength low-alkali Portland cement according to claim 1, characterized in that: In step S1, the chemical composition of the raw material is 41.5-42.5% calcium oxide, 12-14% silicon dioxide, 2.5-3.5% aluminum oxide, 2.3-2.6% iron oxide, 0.1-0.15% sodium oxide, 0.2-0.3% potassium oxide, and 1.0-2.0% magnesium oxide.

3. The method for preparing high-strength low-alkali silicate cement according to claim 1, characterized in that: In step S3, a preheater is used to preheat the air, and the oxygen content of the air at the outlet of the preheater is controlled to be 2%-3.5%.

4. The method for preparing high-strength low-alkali silicate cement according to claim 1, characterized in that: In step S3, the combination is pre-calculated based on the chemical composition of the raw material and the chemical composition of the hazardous waste material to adjust the sulfur-alkali ratio during the clinker calcination process, and the sulfur-alkali ratio in the final clinker is controlled to be 0.8-1.0%.

5. The method for preparing high-strength low-alkali Portland cement according to claim 1, characterized in that: In step S3, the coal ash sedimentation rate during the calcination process is controlled to be 2.1-2.8%.

6. The method for preparing high-strength low-alkali Portland cement according to claim 1, characterized in that: In step S3, the hazardous waste material is composed of any of sludge, organic solvent, filter residue, distillation residue, activated carbon, waste oil, waste and waste liquid.

7. The method for preparing high-strength low-alkali Portland cement according to claim 6, characterized in that: In step S3, the mass proportions of the various components in the hazardous waste material are 50-60% sludge, 0-1% organic solvent, 10-15% filter residue, 3-12% distillation residue, 0-2% activated carbon, 3-6% waste oil, 0-1% waste, and 5-10% waste liquid.

8. The method for preparing high-strength low-alkali Portland cement according to claim 7, characterized in that: In step S3, the chemical composition of each component in the hazardous waste material is: Sludge: Al2O3 0-7%, CaO 0-5%, Fe2O3 0-6%, K2O 0-1%, SiO2 0-8%, Cl 0-1%, S 0-1%, Cr 0-0.045%; Organic solvent: Al2O3 0-7%, CaO 0-3%, Fe2O3 0-4%, K2O 0-1.3%, SiO2 0-7%, Cl 0-1%, S0-1%, Cr 0-0.045%; Filter residue: Al2O3 0-12%, CaO 0-13%, Fe2O3 0-50%, K2O 0-1%, SiO2 0-7%, Cl 0-5%, S 0-5%, Cr 0-0.4%; Distillation residue: Al2O30-7%, CaO 0-2%, Fe2O30-0.1%, K2O 0-3%, SiO20-5%, Cl 0-1%, S0-1%, Cr 0-0.045%; Activated carbon: Al2O3 0-11%, CaO 0-12%, Fe2O3 0-6%, K2O 0-5%, SiO2 0-8%, Cl 0-1%, S 0-1%, Cr 0-0.045%; Waste oil: Al2O3 0-4%, CaO 0-4%, Fe2O3 0-5%, K2O 0-3%, SiO2 0-10%, Cl 0-1%, S 0-1%, Cr 0-0.045%; Waste: Al2O3 0-4%, CaO 0-0.2%, Fe2O3 0-0.15%, K2O 0-1%, SiO2 0-3%, Cl 0-1%, S 0-1%, Cr 0-0.045%; Waste liquid: Al2O3 0-7%, CaO 0-4%, Fe2O3 0-4%, K2O 0-5%, SiO2 0-7%, Cl 0-1%, S 0-1%, Cr 0-0.045%.

9. The high-strength low-alkali Portland cement prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The strength grade of this cement is not less than 42.5.